“Baburnama” And the Genealogy of the Timurides (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article talks about the information layer of the family tree of Timurids in "Baburnama". Information related to the lives of Timurid princes in written sources will serve to further supplement our knowledge about the Timurid genealogy.